FEATURES OF THE NEW PRICING SYSTEM IN THE ROAD SECTOR AND WAYS TO IMPROVE IT - Artem Bezuglyi; Ihor Hresko; Mariia Boyko; Yuliya Bibyk (Дороги і мости, 2023)
Introduction. The new approach to determining the cost of road works and services is adapted to international standards of costs formation in the road sector, and the changes provided by the pricing system will be implemented by all participants of the road sector.